1995
DOI: 10.1128/mcb.15.8.4606
|View full text |Cite|
|
Sign up to set email alerts
|

Presence of Exon Splicing Silencers within Human Immunodeficiency Virus Type 1 tat Exon 2 and tat-rev Exon 3: Evidence for Inhibition Mediated by Cellular Factors

Abstract: Human immunodeficiency virus type 1 (HIV-1)pre-mRNA splicing is regulated in order to maintain pools of unspliced and partially spliced viral RNAs as well as the appropriate levels of multiply spliced mRNAs during virus infection. We have previously described an element in tat exon 2 that negatively regulates splicing at the upstream tat 3 splice site 3 (B. A. Amendt, D. Hesslein, L.-J. Chang, and C. M. Stoltzfus, Mol. Cell. Biol. 14:3960-3970, 1994). In this study, we further defined the element to a 20-nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
149
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 65 publications
6
149
2
Order By: Relevance
“…Among these, the abundant hnRNP A1 protein has been extensively characterized. The first hnRNP A1-dependent ESS was identified in studies of HIV tat exon 2 repression (7)(8)(9). This ESS was found to bind hnRNP A1, and mutations disrupting the ESS prevented hnRNP A1 binding and allowed enhanced exon 2 splicing.…”
mentioning
confidence: 99%
“…Among these, the abundant hnRNP A1 protein has been extensively characterized. The first hnRNP A1-dependent ESS was identified in studies of HIV tat exon 2 repression (7)(8)(9). This ESS was found to bind hnRNP A1, and mutations disrupting the ESS prevented hnRNP A1 binding and allowed enhanced exon 2 splicing.…”
mentioning
confidence: 99%
“…The combination of these various sites gives rise to at least 35 different mRNAs (1). Although the relative efficiencies of the HIV-1 donor sites seem to depend mainly upon their complementarity to the U1 snRNA 5Ј-terminal sequence (3,4), efficiencies of HIV-1 acceptor sites depend upon the presence of cis-regulatory elements (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies have shown that HIV-1 acceptor sites are suboptimal as follows.…”
mentioning
confidence: 99%
“…ESS2 and ESS2p are located within tat exon 2 (3,14), ESS3 is located within tat exon 3 (10,(15)(16)(17)(18), ESSV is located in the vif coding region (19), and an intronic splicing silencer (ISS) is located in the intron upstream of tat exon 3 (13). In a previous study we showed that hnRNPs of the A/B family bind ESS2 to repress splicing of the upstream intron (34).…”
mentioning
confidence: 99%